2020
DOI: 10.3390/foods9010061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Starches on the Rheological, Sensory and Storage Attributes of Non-fat Set Yogurt

Abstract: This study was conducted to investigate the effect of various native starches on the rheological and textural properties of non-fat set yogurt. The yogurt samples were prepared while using five types of starches (potato, sweet potato, corn, chickpea, and Turkish beans). The physical properties of the prepared yogurt were analyzed while using shear viscosity, viscoelasticity, and texture analysis. The tests were performed after 0, 7, and 15 days storage. The effect of these starches on the yogurt viscoelastic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 24 publications
5
34
2
Order By: Relevance
“…Based on the data in Table 1, set yogurt containing PS had unchanged viscosity throughout the storage period; therefore, it can be the best choice for high viscosity set yogurt. is was true when only starch was used as reported by Saleh et al [34]. is indicates no significant interaction between PS and K-casein in the presence of okra gum.…”
Section: Shear Viscositymentioning
confidence: 73%
See 1 more Smart Citation
“…Based on the data in Table 1, set yogurt containing PS had unchanged viscosity throughout the storage period; therefore, it can be the best choice for high viscosity set yogurt. is was true when only starch was used as reported by Saleh et al [34]. is indicates no significant interaction between PS and K-casein in the presence of okra gum.…”
Section: Shear Viscositymentioning
confidence: 73%
“…erefore, for short storage time, it is recommended to use SPS, and for longer storage period, CP is more effective. In previous work, Saleh et al [34] reported the effect of starches only on the set yogurt yield stress and found starches with higher amylose content were less effective in producing firmer gel. In this work, CP which is high in amylose content was the most effective especially at longer storage.…”
Section: Shear Viscositymentioning
confidence: 99%
“…Saari et al (2019) studied the adsorption behaviour of hydrophobically modified starch at oilin-water interfaces during emulsification and found that the OSA could be used as an emulsifier within the given concentration range. However, to date, there is no research about AC used in OWE, but a few studies have investigated its application in yoghurt, dairy desserts and cheese (Saleh et al 2020). However, more investigation of a milk protein-MTS interaction effect in such an emulsion on fat particle size and in the creaming phenomenon is still needed since different modified starches might give different results for the emulsion stability when applied with different milk protein types.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there is no research about AC used in OWE, but a few studies have investigated its application in yoghurt, dairy desserts and cheese (Saleh et al . 2020). However, more investigation of a milk protein‐MTS interaction effect in such an emulsion on fat particle size and in the creaming phenomenon is still needed since different modified starches might give different results for the emulsion stability when applied with different milk protein types.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of the flours caused a modification of the concentration of mineral compounds, with connected increase of some valuable elements, and of the sensory characteristics. Saleh et al [ 7 ] investigated the use of different types of starch (corn, sweet potato, potato, Turkish beans, and chickpea) as fat replacer in set yogurt. The results show that all starches used reduced syneresis and improved firmness of the product, but at different level due to their origin and amylose content.…”
mentioning
confidence: 99%